Predicting the Level of Technical Performance of Rope Skills in Rhythmic Gymnastics in the Light of the Anthropometric Variables of Students of the Faculty of Physical Education - Abdlelah Abdlhusen, Hadeel; Abdulzahra Badr, Nahidah (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to identify the relationship between anthropometric variables, the level of technical performance skills, the athletic gymnastics cord and rhythmic students in the Faculty of Physical Education and Sports Science, and predictive equations of the level of technical performance skills with gymnastics and rhythmic rope. In terms of anthropogenic variables, the researcher used the descriptive method Tan, and like a sample of 34 students from the Faculty of Research in the College of Physical Education and Sports Science, the researchers concluded that there is a relationship between the anthropometric variables. The level of technical performance of the rhythmic gymnastics skills of the athletic rope contributes to the anthropometric changes reached by the researcher Tan, which is an important criterion in determining the level of technical performance of female students in the rhythmic gymnastics of rope skills, and access to the equations of human responses and their regression in the level of skill performance